Obituário - David Zurab Gotsiridze - Scliar-Cabral, Leonor (Signo, 2022)
With great sadness, we received the news that on January 14, 2022, the President of the 11th ISAPL International Congress, held in Tbilisi, Georgia, on June 27-30, 2016, Prof. David Gotsiridze, passed away. We will never forget the generosity with which he welcomed the participants, his constant presence from our arrival in Tbilisi until we left Georgia. Graduated from Tbilisi State University (TSU) at the Faculty of Philology in 1974, Prof. Gotsiridze has worked there since 1978 and he obtained the title of Doctor of Philology in 1987, becoming the Head of the Institute of Slavic Studies (1987-2006), belonging to the Faculty of Humanities, at the Ivane Javakhishvili Tbilisi State University. The position of Professor was obtained in 1989. From 2006-09, he worked at Batumi Shota Rustaveli State University. Prof. Gotsiridze has been also ISAPL President (2013-2016), ellected by the General Assembly, during the 10th ISAPL International Congress, held in Moscow: Until the end of his fruitful days, he contributed decisively to the participation in activities promoted by ISAPL, such as when he organized the Round Table "Psycholinguistic Aspects of Communicational Ethno Style in Art Communication" for the ONLINE ISAPL 12th International Congress. For the monograph "Essays on the History of Russian Grammatical Thought" (co-author, Prof. G. Khukhuni), Prof. Gotsiridze was awarded the Leningrad State University Science Prize (1984). He also received awards on the history of the Russian and Western European period (Tbilisi, 1986); Principles of Contrasting Research of Phrase Texts (in Der Text und seine Struktur [Text and its Structure], Jena, 1990); Revival and Reformation in the history of translation and translational thoughts, Tbilisi, 1994; Russian Linguistic Thought for the First Third Century, Tbilisi, 2000. ISAPL pays tribute to the unforgettable image of Prof. David Gotsiridze.